2020 ASEE North Central Section Conference Proceedings
DOI: 10.18260/1-2--35748
|View full text |Cite
|
Sign up to set email alerts
|

The effects of employment on undergraduate student academic performance

Xinyu Zhang,
Liangcheng Yang

Abstract: This paper reviewed previous studies conducted in multiple countries on the effect of employment on undergraduate student academic performance. This review focuses on understanding the population and characteristics of students taking jobs while studying, the positive and negative effects of paid work on student academic performance, and if there is a threshold of work hours. It was found that a high percentage range, 27.2-97 percent, of college students were reported to take jobs while studying, with the main… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…While some studies have found no significant correlation between employment and academic performance (Sinaga, 2018), others have reported a negative relationship (Baert et al, 2017). There is also evidence that the impact of employment on academic performance may vary depending on various factors, including the type and intensity of work, as well as individual characteristics of students (Zhang & Yang, 2020). It is important to note that certain factors may moderate the negative impact of work on academic performance.…”
Section: Perks and Setbacks Of A Working Studentmentioning
confidence: 99%
See 4 more Smart Citations
“…While some studies have found no significant correlation between employment and academic performance (Sinaga, 2018), others have reported a negative relationship (Baert et al, 2017). There is also evidence that the impact of employment on academic performance may vary depending on various factors, including the type and intensity of work, as well as individual characteristics of students (Zhang & Yang, 2020). It is important to note that certain factors may moderate the negative impact of work on academic performance.…”
Section: Perks and Setbacks Of A Working Studentmentioning
confidence: 99%
“…Recent literature suggests a positive relationship between classroom engagement and academic performance among working students. A study by Zhang and Yang (2020) reported that working students who were highly engaged in their coursework had better grades and were likelier to persist in their studies. Classroom engagement enhances their academic performance and increases their likelihood of staying committed to their academic journey.…”
Section: Classroom Engagement and Academic Performancementioning
confidence: 99%
See 3 more Smart Citations